2021
DOI: 10.1093/workar/waab017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Transfer Between Younger and Older Employees: A Temporal Social Comparison Model

Abstract: Knowledge transfer between younger and older employees can help to prevent organizational knowledge loss and contribute to business success. However, despite its potential benefits, knowledge transfer does not occur automatically. To better understand the challenges associated with age-diverse knowledge transfer, we develop a conceptual model outlining 10 propositions. Specifically, we adopt a temporal social comparison perspective suggesting that employees compare their current and future status (i.e., the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 132 publications
3
42
1
Order By: Relevance
“…One way to increase psychological capital is to pay attention to mature workers’ aging experiences. Organizations may design work for mature workers to enable learning and personal development but also allow social exchange between coworkers (Fasbender & Gerpott, 2021; Fasbender & Gerpott, 2022), which in turn should benefit mature workers’ aging experiences (i.e., enhanced personal growth and self‐knowledge, but reduced social loss).…”
Section: Discussionmentioning
confidence: 99%
“…One way to increase psychological capital is to pay attention to mature workers’ aging experiences. Organizations may design work for mature workers to enable learning and personal development but also allow social exchange between coworkers (Fasbender & Gerpott, 2021; Fasbender & Gerpott, 2022), which in turn should benefit mature workers’ aging experiences (i.e., enhanced personal growth and self‐knowledge, but reduced social loss).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into trust and willingness have enjoyed the greatest popularity in the existing literature on relationships between knowledge sender and receiver. In the KTOYE context, older employees' future time at work is limited, making them willing to pass on their knowledge to fulfill the requirements of guiding younger colleagues (Doerwald et al, 2021 ; Fasbender and Gerpott, 2021 ). By comparison, younger ones have accumulated far less knowledge, thus expressing more willingness to receive knowledge from older employees to satisfy achievement needs at work (Kooij et al, 2011 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…It has been previously observed that the knowledge-based behaviors of recipients form the beliefs and attitudes of sharers, enabling the sharer to behave accordingly (Lichtenstein and Hunter, 2006 ). PB signifies that younger workers accord particular importance to the knowledge of older employees, making the old feel confident since their knowledge and skills are valued (Fasbender and Gerpott, 2021 ), and in turn ardently share more knowledge with the young.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with this trend, an emerging and important question is how organizations can retain older workers who are eligible for retirement to avoid labor shortages, preserve organizational memory, and improve competitiveness (Fleischmann et al, 2015; van Dalen et al, 2015). On the one hand, retirement-eligible workers provide stability in the organization’s knowledge structure and possess rich work experiences and valuable knowledge that are transferable to younger colleagues (Beier & Kanfer, 2013; Burmeister & Deller, 2016; Fasbender & Gerpott, 2022). On the other hand, once older workers have reached retirement age or social security eligibility age, they are eligible to exit the workforce and may be hesitant to stay in the current organization due to various challenges and constraints (e.g., unexpected technological demands; Berg & Piszczek, 2022; Sheng et al, 2022).…”
mentioning
confidence: 99%